ANALISIS METODE ALTMAN Z – SCORE DAN SPRINGATE TERHADAP PREDIKSI FINANCIAL DISTRESS PADA PT. POS INDONESIA PERIODE 2017 – 2023 - Rudi Sanjaya; Ina Nurhidayah (RJABM (Research Journal of Accounting and Business Management), 2025)
This study aims to analyze the potential level of financial distress in PT. Pos Indonesia during the period 2017–2023 using two prediction models: Altman Z-Score and Springate. It also seeks to compare the accuracy levels of both models in predicting financial distress. Financial distress is a condition before bankruptcy that can harm many parties if not anticipated. This research uses a descriptive quantitative method with secondary data sourced from the company’s official annual reports. The results show that based on the Altman Z-Score model, PT. Pos Indonesia falls under the grey area category, indicating it is not yet bankrupt. However, according to the Springate model, the company is considered financially distressed. Of the two models, the Altman Z-Score demonstrates the highest accuracy at 42.58%, making it more reliable for predicting financial distress in this company.